Sustainable development goals performance measurement for OPEC member countries using gray relational analysis method - Keskin, Burak (Frontiers in Sustainability, 2025)
The Sustainable Development Goals (SDGs), announced by the United Nations (UN) in 2015, consist of 17 goals. Today, the rapid increase in population and industrialization necessitates the efficient and effective use of resources. Furthermore, climate change and global warming highlight the importance of a sustainable world. From this perspective, the performance of OPEC (Organization of the Petroleum Exporting Countries) member countries—which hold over two-thirds of the world's oil reserves—in achieving the SDGs is of significant interest. This study uses Gray Relational Analysis (GRA) to examine the performance of 13 OPEC countries using social, environmental, and economic indicators. The results indicate that the countries with the best performance are the United Arab Emirates (UAE), Saudi Arabia, and Kuwait, while those with the lowest performance are Nigeria, Equatorial Guinea, and Angola, respectively. The primary factors contributing to the low performance of certain countries include shortcomings in gender inequality, education, and mortality rate indicators.